Republic of Madagascar : Poverty Reduction Strategy Paper Annual Progress Report; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2006)
The Annual Progress Report (APR) candidly indicates that the macroeconomic objectives for 2005, notably pertaining to growth and revenue objectives, could not be achieved. Looking forward, the preparation of the Madagascar Action Plan (MAP) will provide a useful opportunity to revisit and improve the country's poverty reduction strategy in light of recent developments and experience. Reasonable progress on the public sector governance agenda was triggered by substantial investments in training and capacity building, in particular in the areas of public financial management, planning, change management, and monitoring and evaluation.